UK-based clinical testing programme for somatic and germline BRCA1/2, ATM and CDK12 mutations in prostate cancer: first results - Helene Schlecht; Emma R Woodward; D Gareth Evans; Fiona Lalloo; George Burghel; Ashwin Sachdeva; Andrew Hudson; Robert Bristow; Omi Parikh (BMJ Oncology)
Objective Germline BRCA2 pathogenic variants (PVs) are known to cause ~4% of prostate cancer, but other homologous repair genes, BRCA1, ATM, PALB2 and Lynch syndrome genes are also involved. Our objective was to assess the contribution of germline and somatic gene variants to prostate cancer.Methods and analysis We reviewed germline/tumour DNA testing from 450 localised or metastatic prostate cancer cases in NW England mainly from 2022 to 2024. ORs for additional genes used detection rates in controls from the BRIDGES study.Results 450 cases underwent BRCA1/2 germline/somatic testing with 2 germline PVs in BRCA1 (0.4%) and 27 in BRCA2 (6.0%)—total 6.4% and 6/328 (1.8%) in ATM. There were 280 metastatic prostate cancer samples tested with 11 (4%) somatic BRCA2 and 7 (2.7%) somatic ATM identified with 1 somatic BRCA1. Total PVs in BRCA2 were 31/280 (11%), including germline and indeterminate. CDK12 somatic PVs were found in 9/220 (4.1%), including 2 digenic with BRCA2 and 2 which were biallelic.Conclusion In this continuous clinical evaluation, BRCA2 is the most frequently identified prostate cancer gene with over 10% involvement in metastatic disease. BRCA2 and CDK12 somatic PVs do not appear to be mutually exclusive. BRCA1 does not appear to be a significant contributor to prostate cancer progression.